2019
DOI: 10.1007/s11920-019-1019-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking Behavior in Attention Deficit/Hyperactivity Disorder (ADHD): a Review of Potential Underlying Mechanisms and of Interventions

Abstract: Purpose of Review Attention deficit/hyperactivity disorder (ADHD) is associated with several forms of risk-taking behavior (RTB). This paper aims to examine the scope of ADHD-related RTB, to highlight potential underlying mechanisms of this association, and to review initial evidence for interventions aimed to treat ADHD-related RTB. Recent Findings Multiple lines of evidence indicate that ADHD is associated with real-life RTB across several domains (e.g., reckless driving, substance use, and unprotected sex),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
5
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 114 publications
5
71
5
4
Order By: Relevance
“…The association between ADHD symptoms and RTB was confirmed by all subsequent exploratory analyses on different symptom clusters of ADHD and different forms of RTB: inattention, hyperactivity, and impulsivity were independently found to predict both interpersonal (e.g., stealing) and health-related (e.g., substance abuse) RTB positively. These findings align with a wealth of literature showing increased real-life RTB like substance abuse, risky driving, gambling, antisocial behavior, and unsafe sex in ADHD populations (see Nigg, 2013;Pollak et al, 2019 for reviews on ADHD and RTB). Additionally, these findings suggest that the association between ADHD and RTB is not limited to a specific cluster of ADHD symptoms or a certain dimension of RTB.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The association between ADHD symptoms and RTB was confirmed by all subsequent exploratory analyses on different symptom clusters of ADHD and different forms of RTB: inattention, hyperactivity, and impulsivity were independently found to predict both interpersonal (e.g., stealing) and health-related (e.g., substance abuse) RTB positively. These findings align with a wealth of literature showing increased real-life RTB like substance abuse, risky driving, gambling, antisocial behavior, and unsafe sex in ADHD populations (see Nigg, 2013;Pollak et al, 2019 for reviews on ADHD and RTB). Additionally, these findings suggest that the association between ADHD and RTB is not limited to a specific cluster of ADHD symptoms or a certain dimension of RTB.…”
Section: Discussionsupporting
confidence: 84%
“…This is the first study to investigate whether need for cognition (i.e., the extent to which one tends towards, and enjoys, analytical thought; Cacioppo & Petty, 1982;Cacioppo et al, 1984) mediates the associations between ADHD symptoms and suboptimal decision making (Dekkers et al, 2018(Dekkers et al, , 2016Mowinckel et al, 2015;Patros et al, 2016), as well as RTB (Nigg, 2013;Pollak et al, 2019). ADHD symptomatology was expected to relate to reduced need for cognition that in turn was expected to result in the use of less complex decisionmaking strategies and increased RTB, presumably due to a diminished tendency to consider all relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…The effect ratio (indirect effect / total effect) indicated that the indirect effect of parental knowledge explained 10.5% and 19.4% of the link between ADHD symptoms and RTB in the first two studies, respectively. This is smaller than the 34.3% that was found by Pollak and colleagues [16], but is still substantial, especially given the broad range of factors that have been associated with the link between ADHD and RTB [7]. As the link between ADHD symptoms and RTB is well-established in the literature [5,7,71], we argue that effects of this magnitude are meaningful.…”
Section: Strengths and Limitationscontrasting
confidence: 53%
“…ADHD is associated with impairment in many domains of daily life [5,6]. For example, ADHD is linked to a wide range of risk-taking behaviors, such as substance abuse, risky driving, gambling problems and sexual risk taking (see [7] for a review). Also, children and adolescents with ADHD encounter more academic problems and have poor learning outcomes relative to their peers without ADHD [8,9].…”
Section: General Introductionmentioning
confidence: 99%
“…This revealed that 25% of the adolescents in the MBID group had a clinical diagnosis: Attention Deficit Hyperactivity Disorder (ADHD; 8), Oppositional Defiant Disorder (ODD; 8), ADHD/ODD (2), parent-child relational problem (2), parentchild relational problem + ADHD (2), parent-child relational problem + ODD (1), behavior disorder not otherwise specified (1), Autism Spectrum Disorder (1), Pervasive Developmental Disorder-Not Otherwise Specified (6), attachment disorder (2), adjustment disorder (1), dyslexia + ADHD (1), and parent-child relational problem + Post-Traumatic Stress Disorder (1). Overall, the majority of this group had comorbid externalizing disorders (ADHD, ODD), which have been related to risk taking (Dekkers et al 2016;Pollak et al 2019).…”
Section: Preliminary Analysesmentioning
confidence: 99%